Wholesale Price and Buyback Contracts under Fairness Concerns and Asymmetric Information: A Case Study of Kalleh Dairy Company, Khuzestan Province Branch - Shekasteband, Pooria; Ahmadirad, Mona; Asadzadeh, Shervin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This paper enhances supply chain coordination by incorporating behavioural considerations into contractual mechanisms. We analyze the performance of wholesale price and buyback contracts, highlighting the impact of fairness concerns on supply chain coordination. Our findings indicate the significant influence of supplier and retailer fairness concerns on order quantity and coordination. The buyback contract facilitates closely aligned coordination, while the wholesale price contract may achieve higher utility but lacks comparable coordination. Transparency in information sharing reduces retailer concerns and improves overall utility and coordination. Incorporating fairness concerns and behavioural considerations into contractual mechanisms also enhance supply chain coordination.